Broadband and mode insensitive multimode interference based mode power splitter for mode division multiplexing. (3rd November 2021) - Chack, Devendra; Hassan, Shamsul; Kumar, Amitesh
Abstract: A mode insensitive mode power splitter (MPS) based on multimode interference has been designed using silicon on insulator. The device supports fundamental and first-order transverse electric (TE) and fundamental transverse magnetic (TM) mode (TE0, TE1, and TM0 ) having minimum excess loss of 0.06 dB at input of 1550 nm wavelength, and less than 0.5 dB for a broad wavelength of 1410–1690 nm. Moreover, the proposed mode splitter has a low mode dependent loss (MDL) of 0.02 dB at 1550 nm and supports broad bandwidth of 280 nm having MDL <0.4 dB. The proposed MPS can be a useful mode division multiplexing component for optical networks.